Maternal death reviews: A retrospective case series of 90 hospital‐based maternal deaths in 11 hospitals in Indonesia. (27th February 2019) - Baharuddin, Mohammad; Amelia, Dwirani; Suhowatsky, Stephanie; Kusuma, Ary; Suhargono, Mohammad Hud; Eng, Benjamin
Abstract: Objective: To determine the factors contributing to hospital‐based maternal deaths in Indonesia, given most women deliver with skilled birth attendants and in health facilities. Methods: A retrospective review of case records examined quality of care issues related to maternal mortality in hospital settings. The review abstracted information from blinded medical records of 90 women who died in 11 hospitals from January to June 2014. Specialists from the Indonesian Society of Obstetrics and Gynecology reviewed abstracted records to determine causes of death and identify contextual factors for these deaths. Results: Seventy‐five of the 90 maternal deaths (83%) reviewed were due to direct obstetric causes. Severe pre‐eclampsia and eclampsia combined were the leading direct cause of death (42%). Human resource/health worker factors were more frequently identified than supply, facility, or infrastructure factors. Ninety percent of maternal deaths were classified as preventable. Conclusion: The review exercise yielded useful information on factors contributing to preventable maternal mortality in hospitals in Indonesia. Results helped focus quality improvement efforts and increased awareness of the value of routine, in‐depth facility‐based maternal death reviews. Abstract : This review exercise of maternal deaths in hospitals identified preventable delays in care provision and produced findings that can expedite facility‐based quality improvement efforts.